Influence of color centers on the luminescent response of radiation-damaged CsI: Tl crystal; Functional Materials; Vol. 25, No. 1 - Yakovlev V. Yu. Viktor Yurjevich; Trefilova L. N. Larisa Nikolaevna; Alekseev V. A. Vadim Aleksandrovich; Karnaukhova A. A. Anna Alekseevna; Shpilinskaya O. V. Olga Viktorovna; Lebedinsky A. M. Aleksey Mikhaylovich; Tarakhno O. Aleksey Mikhaylovich (2018, 2018)
Title screen